PULMONARY AMEBIASIS COMPLICATED WITH MASSIVE LEFT EMPYEMA AND RESPIRATORY FAILURE: A CASE REPORT - Dewi P Kristin; Suci D Yulia; Dewi P Ivana; Iswanto Iswanto (Sanamed, 2020)
Introduction: Amebiasis is defined as a parasitic infection with the protozoan Entamoeba histolytica. Amebiasis in pulmonary and pleural tissue is the second common location of extraintestinal amebias is after amoebic liver abscess. Pulmonary and pleural amebiasishappens in 2-3% of invasive amebiasis patients with mortality rate 5-16%.